Knowledge and Behavior of Community Waste Management Pa Mai Ngam Sub-district, Mueang District, Nong Bua Lamphu Province - Klnchampa, Natsaphong; Lamkham, Danai; Promakotr, Rattapon; Sriwicha, Nittaya (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2020)
Waste was important problems in worldwide such as Thailand, it needed a good waste eradication for the health of people. The objectives of this research were to study knowledge and behaviors, to compare the behaviors of community waste management, correlation analysis between knowledge and behaviors of community waste management. For development the guideline to solve the problems of community waste management of Mai Ngam subdistrict, Mueang district, Nong Bua Lamphu province. Cross-sectional survey research was conducted. Of 301 persons were recruited in the study. Questionnaire that including 3 parts was used for data collection. Descriptive statistics including mean, percentage and standard deviation were used for data analysis. Statistic t-test, F-test and pearson’s product moment correlation coefficient was applied to compare knowledge and behavior on waste management of Mai Ngam subdistrict, Mueang district, Nong Bua Lamphu province. The results revealed that knowledge and understanding on waste management of people in Mai Ngam subdistrict, Mueang district, Nong Bua Lamphu province were moderate level about 182 persons (60.26 percentage). For overall of behaviors on waste management were moderate level ( = 3.16, S.D. = 1.27), mean of aspect of reuse had the highest score. There was moderate level ( = 3.35, S.D. = 1.26). Waste management behaviors were compared, the results found that education level, occupation, and income were difference between groups significantly (95%CI). Sex and age were not difference between groups. Knowledge associated waste management behavior. Consequently, increasing knowledge improved great behaviors significantly (r = 0.35) with 95% CI. The study recommended that knowledge of waste management should be trained. Moreover, hazard and impact for each type of waste should be explained, and promoted recycle products and appropriated method to destroy waste were done.